COLLABORATIVE ELECTORAL GOVERNANCE DI PROVINSI NUSA TENGGARA BARAT - lombok, agus; Ansori, Zakaria (Politea : Jurnal Politik Islam, 2024)
This article explores election management practices using a collaborative governance method, focusing on the 2019 election in NTB Province. The study employs a qualitative case study approach, drawing on the governance paradigm and collaborative governance theory. Findings reveal that election management in NTB implemented a hepta-helix collaboration model involving seven actors: election organizing institutions, government, businesses, NGOs, mass media, universities, and political parties. Unlike typical collaborative governance, decision-making in this context remains the prerogative of election organizers, while other actors provide functional support. A critical limitation of this approach is the lack of clear categorization and functional mapping of stakeholders. The study recommends grouping actors into primary, key, and secondary stakeholders, each with defined, mutually supportive roles. Such a structured application of collaborative governance could enhance efficiency and stakeholder synergy. This research contributes to the evolving framework of collaborative governance in election management, enriching the contingency model by Ansell and Gash. By emphasizing structured actor integration, the study offers practical insights into optimizing stakeholder collaboration, ensuring that diverse contributions align with election integrity and transparency goals.